Gravity affected break-up of laminar threads at low gas-relative-velocities - Mescher, Axel; Möller, Arne; Dirks, Martin; Walzel, Peter (Chemical engineering science, 2012)
Due to gravity, initially slow threads are significantly attenuated until break-up occurs. In our experiments these threads are further subject to a gas cross-flow, covering the range of low gas-relative-velocities (<10 m/s). Thread contour data as well as information on the droplet size distribution (DSD), formed under these conditions, are obtained by a shadow-graphic method. The experimental results on the break-up length of the threads confirm the results of former investigations. In contrast, for the mean drop size an unexpected dependency on the gas-relative-velocity is observed, as larger droplets were found for intensified cross-flows. The width of the DSD was found to be also sensitive on the gas-relative-velocity. Even slightly intensified gas cross-flows distinctly increase the poly-dispersity of the DSD. ► Even low gas-relative-velocities influence the break-up of liquid threads. ► Break-up length, mean drop size and the width of DSD depend on the gas-influence. ► Gas–liquid interaction causes larger mean drop size and a broader distribution. ► In technical applications the gas-influence on the threads should be prevented.